IDENTIFICATION OF MAJALAYA COMMON CARP STRAINS RESISTANT TO KHV INFECTION USING CYCA-DAB1*05 ALLELE AS THE MARKER - Alimuddin Alimuddin; Mubinun Mubinun; Ayi Santika; Odang Carman; Irvan Faizal; Komar Sumantadinata (Indonesian Aquaculture Journal, 2011)
The Cyca-DAB1*05 allele of major histocompatibility complex class II genes is recently suggested to have a link with the European common carp strain resistant to koi herpesvirus (KHV). In this study, a set of specific primers for Cyca-DAB1*05 was designed and applied as a marker to identify broodstocks of majalaya common carp strain subsequently used as a candidate resistant to KHV infection. From a total of 23 broodstock subjected to PCR analysis, two female and male fish, both having (P) and no Cyca-DAB1*05 (N), were selected and then diallelly mated. Disease resistance of progenies from 10 crosses was determined by a survival analysis in pond rearing and a laboratory challenge-test using cohabitation method. The results have revealed that the average survivals of PxP progenies for pond rearing and KHV challenge test were 86% and 100% higher (P < 0.05) respectively compared to that of NxN fish. Survival rate of PxN/NxP progenies was significantly lower (P < 0.05) than that of PxP fish. Furthermore, PCR analysis showed that almost 91% progenies of PxP crosses seemed to have a KHV resistant gene marker. Thus, this study suggests that the marker is associated with the KHV resistance in majalaya common carp strain, and farming of PxP progenies can be useful to increase common carp production.